Cathepsin K Deficiency Impaired Ischemia-Induced Neovascularization in Aged Mice - Xueling Yue; Haiying Jiang; Ying Xu; Manli Xia; Xian-Wu Cheng (Stem Cells International)
Background. Aging is a major risk factor for cardiovascular disease. Cysteine protease cathepsin K (CatK) has been implicated in the process of angiogenesis, but the exact roles of individual CatK in vessel formation during aging are poorly understood. Methods and Results. To study the putative role of CatK in ischemia-induced angiogenesis, we applied a hindlimb ischemia model to aged wild-type (CatK+/+) and CatK-deficient (CatK−/−) mice. A serial laser Doppler blood-flow analysis revealed that the recovery of the ischemic/normal blood-flow ratio in the aged CatK−/−mice was impaired throughout the follow-up period. On postoperative day 14, CatK deficiency had also impaired capillary formation. CatK deficiency reduced the levels of cleaved Notch1, phospho-Akt, and/or vascular endothelial growth factor (VEGF) proteins in the ischemic muscles and bone marrow-derived c-Kit+ cells. A flow cytometry analysis revealed that CatK deficiency reduced the numbers of endothelial progenitor cell (EPC)-like CD31+/c-Kit+ cells in the peripheral blood as well as the ischemic vasculature. In vitro experiments, CatK−/− impaired bone-derived c-Kit+ cellular functions (migration, invasion, proliferation, and tubulogenesis) in aged mice. Our findings demonstrated that aging impaired the ischemia-induced angiogenesis associated with the reductions of the production and mobilization of CD31+/c-Kit+ cells in mice. Conclusions. These findings established that the impairment of ischemia-induced neovascularization in aged CatK−/− mice is due, at least in part, to the reduction of EPC mobilization and the homing of the cells into vasculature that is associated with the impairment of Notch1 signaling activation at advanced ages.